1967
DOI: 10.1136/bmj.2.5550.468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandin E1 on platelet behaviour in vitro and in vivo.

Abstract: contraction between the body of the left ventricle and the papillary muscles, which leads to mitral regurgitation, rapid decompression of the left ventricle, and concentric hypertrophy. The importance of outflow tract obstruction and the possible contribution of excessive catecholamines within the heart in producing an abnormally powerful and rapid contraction of the left ventricle are debated.It is concluded that while lesions which produce eccentric hypertrophy do not usually involve the papillary muscles or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

1970
1970
1989
1989

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(36 citation statements)
references
References 11 publications
2
31
0
3
Order By: Relevance
“…In later experiments uptake was determined after incubation for 1 h. As adrenaline can cause aggregation of platelets in plasma, prostaglandin E1 (2-8 x 10-7M) which had no effect on adrenaline uptake (Table 1) the platelet-rich plasma to inhibit aggregation (Emmons, Hampton, Harrison, Honour & Mitchell, 1967). The uptake of intact [3H]-adrenaline was proportional to the concentration of extracellular adrenaline up to about 1 x 10-4M; with higher concentrations the proportionality decreased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In later experiments uptake was determined after incubation for 1 h. As adrenaline can cause aggregation of platelets in plasma, prostaglandin E1 (2-8 x 10-7M) which had no effect on adrenaline uptake (Table 1) the platelet-rich plasma to inhibit aggregation (Emmons, Hampton, Harrison, Honour & Mitchell, 1967). The uptake of intact [3H]-adrenaline was proportional to the concentration of extracellular adrenaline up to about 1 x 10-4M; with higher concentrations the proportionality decreased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Emmons, Hampton, Harrison, Honour & Mitchell (1967), first demonstrated that PGE1 inhibits platelet thrombus formation in vivo in injured rabbit-brain arteries. Westwick (1977) has now shown that both PGE1 and PGG2 inhibit thrombus formation in hamster cheek pouch arterioles.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds which affect the activity of these enzymes and, as a result, the concentrations of adenosine 3',5'-monophosphate (cyclic AMP, cAMP) in platelets also have marked effects on platelet aggregation (2, 6-10) and on the platelet release reaction (11). For example, incubation of platelets with prostaglandin (PGE1), N6-2'-0-dibutyryl cyclic adenosine 3',5'-monophosphate (DBcAMP), or theophylline before addition of thrombin inhibits thrombin-induced platelet aggregation (9,10,12) and release (11). These observations have led to the hypothesis that agents which inhibit platelet aggregation increase the concentration of cAMP in platelets by stimulating adenyl cyclase or by inhibiting cAMP phosphodiesterase, and agents which stimulate aggregation and release, decrease platelet cAMP by the opposite mechanisms.…”
Section: Introductionmentioning
confidence: 99%